Polysaccharide-based biodegradable hydrogel adsorbents for sustainable water treatment: Functional enhancements and environmental sustainability – a critical review - Ros Azlinawati, Ramli; Abd El-Fattah, Wesam; Sillanpaa, Mika; Guesmi, Ahlem; Ben Hamadi, Naoufel (Elsevier Ltd., 2026)
Water pollution poses a critical global threat to public health, ecosystems, and sustainable development, necessitating innovative and environmentally responsible water treatment technologies. Among various approaches, adsorption stands out for its efficiency, cost-effectiveness, and operational simplicity, with biodegradable hydrogel adsorbents recently emerging as promising candidates due to their tunable physicochemical properties, biodegradability, and high adsorption capacity. However, large-scale feasibility, long-term stability, environmental safety, degradation behaviours, and life cycle sustainability assessments remain underexplored, creating a significant research gap. This review critically examines recent advancements in functionalized biodegradable hydrogel adsorbents for water treatment, highlighting chemical modifications, nanocomposite integration, and stimuli-responsive designs that enhance adsorption efficiency, selectivity, and reusability. By integrating insights from materials science, environmental engineering, and green chemistry, this study provides a comprehensive understanding of functional enhancements, environmental sustainability considerations, and industrial translation prospects. Ultimately, the review offers a roadmap for next-generation hydrogel adsorbents, promoting their role as sustainable and high-performance materials for future water purification technologies